The Art of Persuading God through Generosity and Miserliness: A Saussurean Semiotic Reading of Q.S. al-Layl (92): 5–11 - Agung Purnomo; Ah. Fawaid (Mashdar: Jurnal Studi Al-Qur'an dan Hadis, 2025)
This study examines three paradoxical phenomena frequently observed in contemporary Muslim societies: generous Muslims who nonetheless endure persistent worldly hardship, miserly individuals who appear outwardly content, and non-Muslims who exhibit notably charitable behaviour. Employing a qualitative, library-based design with documentation as its primary data-gathering method, the study applies Ferdinand de Saussure's structural semiotics through four analytical stages: langue–parole, signifier–signified, synchronic–diachronic, and syntagmatic–paradigmatic relations, to reinterpret Q.S. al-Layl (92): 5–11. The findings reveal that when generous Muslims who affirm divine recompense continue to experience worldly difficulty, this reflects an unfulfilled dimension of taqwā, whereby the promised ease is deferred to the hereafter while hardship persists in the present life. Conversely, non-Muslims who practise generosity without faith receive their worldly ease in full, yet face adversity in the eschatological realm. The apparent happiness of miserly individuals – Muslim and non-Muslim alike– proves illusory and transient, masking deeper forms of suffering that manifest as social disintegration in this world and punitive consequences in the hereafter. Such miserliness further cultivates arrogance, perceived self-sufficiency, anxiety over material loss, and a fundamental rejection of the principle of divine recompense. These findings underscore that ease and hardship, as articulated in Q.S. al-Layl (92): 5–11, operate across both temporal and eschatological dimensions and cannot be assessed solely through observable worldly outcomes.